Fine needle aspiration cytology of breast cancer in women aged 70 years and older - Tse G.M.K. (2014)
Aims: Elderly breast cancers are associated with a more favourable biological marker profile and higher proportion of specific subtypes, some of which are of low histological grade. We reviewed the fine needle aspiration cytology (FNAC) to assess the cytological characteristics and any clues to assist in the diagnosis. Methods: The aspirates of 140 cancers of various histological types and grades and 39 benign lesions were evaluated for 13 cytological parameters including cellularity of the direct and cytospin smears, epithelial cell clusters, cellular atypism, cytoplasmic features, vacuoles, mitotic figures, presence of myoepithelial cells, single background epithelial cells, the presence of naked nuclei, stromal fragments and necrosis. Results: We found that the presence of background single epithelial cells, atypism of such cells, absence of benign appearing epithelial fragments, nuclear atypism of the epithelial cells within the fragments, presence of moderate amount of cytoplasm of these cells, absence of myoepithelial cells within the cluster, and absence of bipolar nuclei in the background have a strong association with malignancy. Scoring only the presence of single cells in the background, single cell atypism and the absence of bipolar nuclei in a scoring system can differentiate between benign and malignant aspirates with high (>90%) sensitivity and specificity. Conclusions: Assessing the presence of single cells in the background, single cell atypism and the absence of bipolar nuclei facilitates identification of malignancy in the aspiration of breast lesions from elderly patients. © 2008 Royal College of Pathologists of Australasia.